Burqas, Baseball, and Apple Pie : Being Muslim in America - Idliby, Ranya Tabari (New York Palgrave Macmillan, 2014)
For many Americans, the words 'American' and 'Muslim' simply do not marry well; for many the combination is an anathema, a contradiction in values, loyalties, and identities. This is the story of one American Muslim family--the story of how, through their lives, their schools, their friends, and their neighbors, they end up living the challenges, myths, fears, hopes, and dreams of all Americans. They are challenged both by Muslims who speak for them and by Americans who reject them. In this memoir, Idliby discusses not only coming to terms with what it means to be Muslim today, but how to raise and teach her children about their heritage and religious legacy.
Include Illustrations and Index
Keywords: United States -- Muslims--Ethnic Identity